2015
DOI: 10.1111/jir.12254
|View full text |Cite
|
Sign up to set email alerts
|

Weight, nutrition, food choice, and physical activity in adults with intellectual disability

Abstract: These findings suggest that people with ID are at risk of developing diseases associated with obesity, inactivity, and poor nutrition. Strategies to encourage people with ID to engage in physical activity and healthy eating are, therefore, a matter of priority and should involve their disability workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 54 publications
(114 reference statements)
0
43
1
4
Order By: Relevance
“…The prevalence of intellectual disabilities is generally estimated between 1% and 2% of the general population (Harris, ; Maulik, Mascarenhas, Mathers, Dua, & Saxena, ) making individuals with intellectual disabilities a substantial interest group for public health. It is well documented that persons with intellectual disabilities have poorer heath status and lower physical activity than the general population (Dixon‐Ibarra, Lee, & Dugala, ; Draheim, ; Haveman et al., ; Koritsas & Iacono, ; Krahn & Fox, ; Naaldenberg et al., ; Peterson et al., ; Stanish, Temple, & Frey, ; Sundahl, Zetterberg, Wester, Rehn, & Blomqvist, ). In fact, the documented differences in health played a role in the recent identification of disability as a health disparity population (Krahn, Walker, & Correa‐De‐Araujo, ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of intellectual disabilities is generally estimated between 1% and 2% of the general population (Harris, ; Maulik, Mascarenhas, Mathers, Dua, & Saxena, ) making individuals with intellectual disabilities a substantial interest group for public health. It is well documented that persons with intellectual disabilities have poorer heath status and lower physical activity than the general population (Dixon‐Ibarra, Lee, & Dugala, ; Draheim, ; Haveman et al., ; Koritsas & Iacono, ; Krahn & Fox, ; Naaldenberg et al., ; Peterson et al., ; Stanish, Temple, & Frey, ; Sundahl, Zetterberg, Wester, Rehn, & Blomqvist, ). In fact, the documented differences in health played a role in the recent identification of disability as a health disparity population (Krahn, Walker, & Correa‐De‐Araujo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers across the world have reported the prevalence of being overweight and obese among adults with intellectual disability to be 28% -71% and 17% -43%, respectively (Barnes, & Echteld, 2012& Echteld, , 2009Emerson, Hatton, Baines, & Robertson, 2016;Haider, Ansari, Vaughan, Matters, & Emerson, 2013;Hsieh, Rimmer, & Heller, 2014;Koritsas & Lacono, 2016;Martínez-Leal et al, 2011;Melville et al, 2008;Mikulovic et al, 2014;Sohler, Lubetkin, Levy, Soghomonian, & Rimmerman, 2009;Stedman & Leland, 2010;Temple, Foley, & Lloyd, 2014;Wallace & Schluter, 2008; Table 1). The evidence is mixed on whether the prevalence of being overweight and/or obese is similar or proportionally higher or lower for individuals with intellectual disability versus the general population.…”
Section: Prevalence Of Being Overweight and Obesementioning
confidence: 99%
“…Koritsas and Lacono (2016) • 60.3% of the study participants with intellectual disability had little choice in the type of food they ate.…”
Section: Hsieh Et Al (2014)mentioning
confidence: 99%
“…Being overweight is an important risk factor for colorectal cancer, with an estimated increased risk of 41% for a body mass index (BMI) > 30 compared to a BMI < 23 [13]. Additionally, PWIDs are less involved in physical activity; a recent Australian study indicated that 60.3% of 68 adult PWIDs did not reach the national physical activity guidelines [14]. Globally, PWIDs are low consumers of alcohol compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, PWIDs are low consumers of alcohol compared to the general population. However, they have a moderate risk of malnutrition, with 17.6% of them in the high-risk category [14]. Constipation, which is clearly more prevalent in children and adults with IDs [15], is currently not considered a risk factor for colon cancer.…”
Section: Introductionmentioning
confidence: 99%